Implikasi Putusan Mahkamah Konstitusi terhadap Calon Kepala Daerah Terpilih Tahun 2024 - Adrianus Bawamenewi (SENTRI: Jurnal Riset Ilmiah, 2025)
The 2024 simultaneous regional head elections in Indonesia highlighted significant legal and administrative challenges, particularly concerning the eligibility requirements of candidate pairs. This study examines the legal implications of Constitutional Court (Mahkamah Konstitusi) Decisions No. 132/PHPU.BUP-XXIII/2025 and No. 195/PHPU.BUP-XXIII/2025, which resulted in the disqualification of elected regent candidates in Tasikmalaya and Kutai Kartanegara. Employing a normative legal research method with a case-based approach, this study analyzes the Court’s interpretation of term limits for regional heads, focusing on whether service as an acting official should be counted toward a full term of office. The findings demonstrate that the Constitutional Court consistently applied a substantive and factual interpretation of tenure, affirming that service exceeding two and a half years—whether as an acting or definitive regional head—constitutes one full term. Consequently, candidates who had effectively served two terms were declared ineligible, their election results were rendered legally void, and the Regional Election Commissions were ordered to conduct re-voting without the disqualified candidates. These decisions produced wide-ranging implications, including administrative annulment of election results, increased financial burdens due to re-elections, political instability at the local level, and challenges for political parties in nominating replacement candidates. This study contributes to electoral practice by clarifying the legal standards for calculating regional head tenure and emphasizing the necessity of rigorous administrative verification by election management bodies. It offers practical recommendations for the General Election Commission and supervisory institutions to strengthen regulatory consistency, prevent misinterpretation of eligibility requirements, and enhance the integrity, legal certainty, and sustainability of future regional elections in Indonesia.